Chronic Alcohol Induces M2 Polarization Enhancing Pulmonary Disease Caused by Exposure to Particulate Air Pollution. (13th June 2013) - Thevenot, Paul; Saravia, Jordy; Giaimo, Joseph; Happel, Kyle I.; Dugas, Tammy R.; Cormier, Stephania A.
Abstract : Background: Chronic alcohol consumption causes persistent oxidative stress in the lung, leading to impaired alveolar macrophage (AM) function and impaired immune responses. AMs play a critical role in protecting the lung from particulate matter (PM) inhalation by removing particulates from the airway and secreting factors which mediate airway repair. We hypothesized AM dysfunction caused by chronic alcohol consumption increases the severity of injury caused by PM inhalation. Methods: Age‐ and sex‐matched C57BL/6 mice were fed the Lieber‐DeCarli liquid diet containing either alcohol or an isocaloric substitution (control diet) for 8 weeks. Mice from both diet groups were exposed to combustion‐derived PM (CDPM) for the final 2 weeks. AM number, maturation, and polarization status were assessed by flow cytometry. Noninvasive and invasive strategies were used to assess pulmonary function and correlated with histomorphological assessments of airway structure and matrix deposition. Results: Co‐exposure to alcohol and CDPM decreased AM number and maturation status (CD11c expression), while increasing markers of M2 activation (interleukin [IL]‐4Rα, Ym1, Fizz1 expression, and IL‐10 and transforming growth factor [TGF]‐β production). Changes in AM function were accompanied by decreased airway compliance and increased elastance. Altered lung function was attributable to elevated collagen content localized to the small airways and loss of alveolar integrity. Intranasal administration of neutralizing antibody to TGF‐β during the CDPM exposure period improved changes in airway compliance and elastance, while reducing collagen content caused by co‐exposure. Conclusions: Combustion‐derived PM inhalation causes enhanced disease severity in the alcoholic lung by stimulating the release of latent TGF‐β stores in AMs. The combinatorial effect of elevated TGF‐β, M2 polarization of AMs, and increased oxidative stress impairs pulmonary function by increasing airway collagen content and compromising alveolar integrity.